Dynamic response analysis on vibration of ground and track system induced by metro operation. Issue 3 (8th April 2019) - Ding, Zhi; Li, Danwei
Abstract : Purpose: This paper aims to evaluate the dynamic response of surrounding foundation and study the vibration characteristics of track system. Design/methodology/approach: A double-line underground coupling analysis model was established, which included two moving train, track, liner and the ground field. Findings: Based on the 2.5D (D is diameter) finite element analysis, the influence of the important factors such as the depth of the subway tunnel, the nature of the foundation soil, the relative position relation of the double tunnel, the subway driving speed on the foundation and the orbital vibration are analyzed in this article. Originality/value: The results in paper may have reference value for the prediction of train induced vibrations and for the research of dynamic response of ground field.